Pattern of Psychosocial Challenges among Oil and Gas Workers: A systematic review - Mohd Rani, Nur Dalilah; Kamarunzaman, Nur Zafifa; Liu, Jia (Environment-Behaviour Proceedings Journal, 2022)
This paper highlights the patterns of psychosocial challenges confronting O&G workers that result in mental health issues worldwide through a systematic review of notable academic databases. This study integrated multiple research designs, and the review was based on the publication standard, namely RepOrting standards for Systematic Evidence Syntheses (ROSES). Thematic analysis was undertaken, and four emerging themes were identified: 1) demographic factors, 2) personality, 3) psychosocial risks, and 4) health conditions. The findings contributed to several theoretical and practical implications, which are essential for researchers in the O&G field and policymakers. Keywords: psychosocial risks; personality; well-being; oil &gas eISSN: 2398-4287 Â© 2022. The Authors. Published for AMER ABRA cE-Bs by e-International Publishing House, Ltd., UK. This is an open access article under the CC BYNC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/). Peerâ€“review under responsibility of AMER (Association of Malaysian Environment-Behaviour Researchers), ABRA (Association of Behavioural Researchers on Asians/Africans/Arabians) and cE-Bs (Centre for Environment-Behaviour Studies), Faculty of Architecture, Planning & Surveying, Universiti Teknologi MARA, Malaysia. DOI: https://doi.org/10.21834/ebpj.v7i20.3491